Regime Change and Malaysia – Japan Relations: Explaining Shifts and Continuity In Foreign Policy - Govindasamy, Geetha; Azman, Muhammad Danial (WILAYAH: The International Journal of East Asian Studies, 2020)
The article offers an initial exploration into the causal linkage between domestic political regime change and foreign policy recalibration in Malaysia. While not popular, the notion that foreign policy objectives are more often than not shaped by internal dynamics is rather true in the Malaysian case. The discussion examines Malaysia’s relations with Japan during the Pakatan Harapan government which began in May 2018 but collapsed by February 2020. After being sworn in as the Prime Minister of Malaysia for the second time, Dr. Mahathir Mohamad pledged to re-energize the Look East Policy to facilitate economic growth and investments into the country. Though the move was far from surprising, the consequence of the development needs to be understood within the broader context of Malaysia’s domestic ties with China. Malaysia’s move to expand cooperation with Japan can be explained by a desire to reduce overreliance on Chinese investments. The basic premise is that Malaysia was not tilting towards Japan, rather the move to court Japan through the LEP 2.0 was a function of regime legitimation through which Pakatan Harapan diversified its foreign policy partners for the goal of expanding investment and collaboration opportunities.